До питання про кримінальну процесуальну регламентацію терміну «електронні активи, одержані злочинним шляхом» - Пчеліна, О. В.; Pchelina, O. V.; Пчеліна Оксана Василівна (Науковий вісник Ужгородського національного університету. Сер.: Право. – 2022. – Вип. 71. – С. 327-332, 2022)
Проаналізовано наукові положення і положення законодавства України та галузевих нормативно-правових актів, встановлено, що в чинному кримінальному процесуальному законодавстві України визначення терміну «електронні активи, одержані злочинним шляхом» не закріплено. Щоб виправити вказану ситуацію та мінімізувати випадки виникнення труднощів під час накладення арешту на електронні активи, одержані злочинним шляхом, у кримінальному провадженні,запропоновано закріпити дефініцію електронних активів, одержаних злочинним шляхом.

In the article it has been emphasized that the effectiveness of criminal proceedings in general and the seizure of such property as electronic assets obtained by criminal means, in particular, depends on understanding the nature of this type of asset and the state of its criminal procedure. It has been emphasized that the researched question acquires special value in the conditions of constant information-technological development and its introduction in all spheres of public life. It has been analyzed the provisions of regulations in which the legislator uses the term “asset”. It has been found that the category “asset” is used in accounting and financial reporting. It has been established that in the tax legislation there is a phrase “assets of an individual”. It has been noted that the legislative interpretation of the term “assets” is given in the Criminal Code of Ukraine, the laws of Ukraine “On the National Agency of Ukraine for Detection, Investigation and Management of Assets Obtained from Corruption and Other Crimes” and “On Prevention and Counteraction to Legalization (Laundering) of Proceeds from Crime, Financing of Terrorism and Financing of the Proliferation of Weapons of Mass Destruction”. It has been stated that at the legislative level the term “electronic assets” has not found its consolidation and settlement. It has been noted that electronic assets are, in fact, financial assets in electronic form. It has been found that the term “obtained by criminal means” is understood. It has been proposed to carry out criminal procedural regulation of the term “electronic assets obtained by criminal means” by supplementing Part 1 of Art. 1 of the Law of Ukraine “On the National Agency of Ukraine for Detection, Investigation and Management of Assets Obtained from Corruption and Other Crimes” by paragraph 11 of the following content: “1-1) electronic assets obtained by criminal means - cash in the form of entries in accounts non-cash form) and virtual assets that are directly or indirectly obtained as a result of a criminal offense and / or are income from such property; intended (used) to persuade a person to commit a criminal offense, financing and / or material support of a criminal offense or reward for its commission; is the subject of a criminal offense; found, manufactured, adapted or used as a means or instrument of committing a criminal offense”.

Проанализированы научные положения и положения законодательства Украины и отраслевых нормативно правовых актов, установлено, что в действующем уголовном процессуальном законодательстве Украины определение термина «электронные активы, полученные преступным путем» не закреплено. Чтобы исправить указанную ситуацию и минимизировать случаи возникновения трудностей при наложении ареста на электронные активы, полученные преступным путем, в уголовном производстве, предложено закрепить дефиницию электронных активов, полученных преступным путем.
On the question of criminal procedural regulation of the term “electronic assets obtained by criminal route”
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; кримінальне провадження; criminal proceedings; уголовное производство; арешт майна; seizure of property; арест имущества; кримінально процесуальна регламентація; criminal procedural regulations; уголовно-процессуальная регламентация; кримінально-процесуальне законодавство; criminal procedural legislation; уголовно-процессуальное законодательство; активи; assets; активы; електронні активи; electronic assets; електронні гроші; electronic money; электронные деньги; електронні активи, одержані злочинним шляхом; электронные активы, полученные преступным путем; electronic assets obtained through criminal means